The Combination Effect Of Quick Feet And Tuck Jump Exercise On Agility And Speed - Muhammad Labib Siena Ar Rasyid; Oce Wiriawan; Gigih Siantoro; Muhammad Muhammad; Wijono Wijono; Taufiq Hidayat (UNIVERSITAS NEGERI MAKASSAR, 2023)
This study aims to reveal the effect of a combination of quick feet (ladder drill) and tuck jump (plyometric) exercises on agility and speed. Quantitative research methods were used in this study with a quasi-experimental research type. The population of this study was extracurricular badminton students at SMPN 1 Jogoroto Jombang, and the sampling technique used was the purposive sampling technique. There were 24 students, and the research sample was divided into two groups with the same number: the group that was given a combination of quick feet and tuck jump (QFTJ) exercises and the group that only did conventional exercises (LK). The treatment was conducted for 18 meetings with details thrice a week for six weeks. This study used an instrument like an agility T-test to measure agility and a 30-meter sprint to measure speed. Data collection was carried out twice, namely before treatment (pretest) and after treatment (post-test). This study used paired sample t-tests and independent sample t-tests as data analysis techniques. The results showed that each group significantly increased agility and speed (p<0.05). However, based on the independent sample t-test, it showed that there was a significant difference between the QFTJ group and the LK group. The conclusion is that the combination of quick feet (ladder drill) and tuck jump (plyometric) exercises significantly increases agility and speed compared to conventional exercises.